2022
DOI: 10.3390/metabo12090856
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of GLUT4 Glucose Uptake by Anthocyanin-Rich Extract from Black Rice (Oryza sativa L.) via PI3K/Akt and AMPK/p38 MAPK Signaling in C2C12 Cells

Abstract: Anthocyanin from black rice was reported to have beneficial effects on diabetes, but the molecular mechanisms are still largely unknown. Black rice cultivated from different regions in Taiwan (Hualien and Changhua) were included in this study. Concentrations of anthocyanin were significantly higher using the ethanol extraction method than those using water; therefore, ethanol extracts from Hualien and Changhua black rice (HBRE and CBRE) were used for further investigation. 2-NBDG glucose uptake analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In general, predicted molecular docking results and experimental results do not always agree well because a variety of factors can be involved, such as uptake, stability, and other interactions of the compounds, but in this study, the experimental results and molecular docking results agree well, suggesting the anti-diabetic potential of gingerglycolipid A. The evaluation of C2C12 cell glucose uptake and the involvement of various molecular factors, such as PPARγ, IRS-1, p-IRS-1, AMPK, and p-AMPK shed light on the intricate regulatory mechanisms that govern glucose homeostasis in skeletal muscle cells [20][21][22]. These factors play significant roles in glucose uptake and insulin sensitivity, and their interactions with, and effects on, metabolic health are significant.…”
Section: Discussionsupporting
confidence: 66%
“…In general, predicted molecular docking results and experimental results do not always agree well because a variety of factors can be involved, such as uptake, stability, and other interactions of the compounds, but in this study, the experimental results and molecular docking results agree well, suggesting the anti-diabetic potential of gingerglycolipid A. The evaluation of C2C12 cell glucose uptake and the involvement of various molecular factors, such as PPARγ, IRS-1, p-IRS-1, AMPK, and p-AMPK shed light on the intricate regulatory mechanisms that govern glucose homeostasis in skeletal muscle cells [20][21][22]. These factors play significant roles in glucose uptake and insulin sensitivity, and their interactions with, and effects on, metabolic health are significant.…”
Section: Discussionsupporting
confidence: 66%
“…Data support that AMPK inhibits Rab-GTPase activating proteins AS160 (TBC1D4) and TBC1D1, which triggers Glut-4 trafficking to the plasma membrane [ 274 ]. Firstly, related to the stimulation of Glut-4 translocation and AMPK activation, a previous study demonstrated that anthocyanin-rich extract from black rice promotes glucose uptake by increasing Glut-4 expression in the plasma membrane in C2C12 myotubes via activation of the PI3K/Akt and AMPK/p38 MAPK pathways [ 275 ]. Furthermore, resveratrol, a naturally occurring phytochemical, increases glucose uptake in insulin-resistant 3T3-L1 adipocytes by increasing pAkt phosphorylation and downstream AMPK activation.…”
Section: A Plant-based Diet and Metabolic Syndromementioning
confidence: 99%
“…Anthocyanin-rich extract from black rice (Oryza sativa L.) extracted with ethanol from Hualien (HBRE) and Changhua (CBRE) region help promotes glucose uptake in C2C12 myotubes by increasing GLUT4 expression and phosphorylation of IRS-1. CBRE increased p-AMPK/AMPK while HBRE involves in PI3K/Akt and MAPK/ERK (Feng et al, 2022).…”
Section: Potential Plant Bioactive Compoundsmentioning
confidence: 89%